Hydrochlorothiazide and risk of melanoma subtypes. Issue 10 (26th May 2021) - Habel, Laurel A.; Achacoso, Ninah; Fireman, Bruce; Pedersen, Sidsel Arnspang; Pottegård, Anton
Abstract: Background: Hydrochlorothiazide (HCTZ), a common diuretic known to be photosensitizing and previously associated with non‐melanoma skin cancer, was recently reported to be associated with two melanoma subtypes, nodular and lentigo, among residents of Denmark. Our goal was to examine whether Danish findings could be replicated in a US cohort, using a similar study design and analysis. Methods: Among non‐Hispanic White enrollees of Kaiser Permanente Northern California, we conducted an analysis of 9176 melanoma cases and 264 781 controls, matched on age, sex and time in health plan. We examined use of HCTZ prior to cancer diagnosis (cases) or comparable date for controls, categorized as never use, ever use and high use (≥50 000 mg). Electronic health records provided data on prescriptions, cancer diagnoses, and covariates. Conditional logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), adjusted for education, income and number of dermatology, internal medicine and urgent care visits. Results: We observed a small increase in risk of melanoma, all types combined, associated with high use (≥50 000 mg) of HCTZ (OR = 1.11, 95% CI 1.00–1.23) and no evidence of a dose–response. Risk was more elevated for lentigo subtype (OR = 1.57, 95% CI 1.01–2.42). The somewhat elevated risk for nodular subtype was not statistically significant (OR = 1.22, 95% CI 0.78–1.90). There was very little association of high use with the superficial spreading subtype (OR = 1.05, 95% CI 0.80–1.37). Conclusions: Our findings support a recent report of an association between high use of HCTZ and increased risk of the lentigo subtype of melanoma.